KAJIAN KONSEP OPEN-AIR MUSEUM: STUDI KASUS KAWASAN CAGAR BUDAYA TROWULAN - Wany Raharjo Wahyudi; Kuswanto Kuswanto (Balai Arkeologi Yogyakarta, 2014)
This article discusses the concept of open-air museum as a kind of museum based on the new museology paradigm, within the heritage region of Trowulan. Research location is in the Heritage Region of Trowulan, Mojokerto, East Java Province. This study is a qualitative research with case studies strategy, and the research stages include data collection, data processing, and data integration (conclusion). The research results can formulate concepts and models of open-air museum that can be developed in the Cultural Heritage Regions of Trowulan. Principally, it is an open-air museum in the form of monumental buildings that located on the original site (in situ) equipped with the interpretation of human activities and integrated in an exhibition layout theme. The exhibition layout theme presented is about multicultural aspects from the Majapahit Kingdom.